Studying the level of visionary leadership of the Athletics Federation from coaches’ point of view - Abdulhussein, Ali; Hani, Ahmed (Journal of Physical Education, 2023)
Environmental changes are forcing the sports leaders to cope with by monitoring changes, creating a future vision for the sports organization’s objectives, and working to deliver them to the followers in their capacity as implementers of the leader’s thought, especially since the human element is the most important resource of the organization’s resources that contributes so as to achieve its objectives. It is important to have leaders who have a clear vision of the objectives of the sports organization and the behavior of the individuals with whom it deals with, especially since behavior is difficult to control because it is affected by emotions and feelings. The effective leader is the one who can move the behavior of the followers towards performing the work entrusted to them with high efficiency. Visionary leadership has become a prerequisite for making good decisions. The importance of the research lies in addressing the topic of visionary leadership, which is relatively new in administrative thought in general, and accompanying it as a leadership for the members of the Athletics Federation. The research aims to identify the level of visionary leadership in the Athletics Federation from the point of view of the coaches. The researchers used the descriptive method with the survey method.The research community consisted of athletics coaches. They numbered (178) coaches. The researcher chose (100) coaches to represent the sample. The researcher concluded that there is a visionary leadership for the Iraqi Athletics Federation, but in a somewhat moderate manner, and that the presidents and members of the Iraqi Athletics Federation need to have a perspective on the future. The researcher recommends strengthening and developing the vision possessed by visionary leaders by holding discussion circles with their colleagues on a topic and searching for new ideas on which to base their new visions.